The Development of Information Website for Master Program in Vocational Education of Universitas Negeri Semarang - Kurniawan, Muhammad; Syamwil, Rodia; Wijaya, M. Burhan Rubai (Universitas Negeri Semarang, 2018)
This study aims to develop a website of Master Study Programs in Vocational Education of Universitas Negeri Semarang (UNNES). This research used Research and Development methods, and website development design using the Waterfall method. The subjects of the study are students, alumni & managers of the Master Study Program at UNNES vocational education. The object of this study is the website of the UNNES Vocational Education Graduate Study Program. The sample of the research subjects was taken purposively because this research focused more on the research objectives, the website applied in this Study Program. The development of this website was tested by validators of web experts, substance experts, and user validators. The test results from the validator are as follows: (1) the test results of web experts got an average percentage of 90% or can be considered very feasible; (2) the results of testing by a substance expert got an average of 88% (very feasible); (3) the test results by the user got an average of 90% or very good. This study program information website was also tested using the blackbox method which resulted in the average website running well in suitted with the results expected. The reliability of the website was tested using loadimpact, tools for stress testing using 50 virtual users for 5 minutes, the results of which failed rate 0. This study produced a web with broadcast message feature, responsive website theme. The final results of research on website development are categorized as very feasible to be applied.